2019
DOI: 10.1542/neo.20-3-e124
|View full text |Cite
|
Sign up to set email alerts
|

When to Include a Lumbar Puncture in the Evaluation for Neonatal Sepsis

Abstract: Infants younger than 1 month are at risk for meningitis and may not present with classic signs such as seizures or a bulging fontanelle. Thus, a lumbar puncture should be considered during an evaluation for sepsis in newborns in specific scenarios. While the presence of bacteremia increases the likelihood of meningitis in infants, approximately one-third of cases of meningitis occur in the setting of negative blood cultures. AbstractMeningitis is a devastating infection in infants and is linked to adverse long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
1
22
0
2
Order By: Relevance
“…Because the majority of neonates with concurrent CNS infection have minimal neurologic findings, 24 a CSF examination is accepted as part of the routine workup, especially for late-onset neonatal sepsis. 25 In some institutions, especially in resource-limited settings in our country, the lengthy turnaround time for diagnostic test results is a major impediment to early commencement of antibiotics that may result in substantial morbidity and neurologic sequelae, especially in the presence of meningitis. On the other hand, empirical antibiotics that provide coverage for a broad spectrum of CNS bacterial pathogens leads to overuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the majority of neonates with concurrent CNS infection have minimal neurologic findings, 24 a CSF examination is accepted as part of the routine workup, especially for late-onset neonatal sepsis. 25 In some institutions, especially in resource-limited settings in our country, the lengthy turnaround time for diagnostic test results is a major impediment to early commencement of antibiotics that may result in substantial morbidity and neurologic sequelae, especially in the presence of meningitis. On the other hand, empirical antibiotics that provide coverage for a broad spectrum of CNS bacterial pathogens leads to overuse.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, clinical assessment alone in this population is of limited value in the prediction of CNS involvement. 25,35…”
Section: Csf and Plasma Have Common Chemicalmentioning
confidence: 99%
“…5 Meningitis is frequently found in LOS cases in comparison to EOS while it is also found that LOS linked meningitis is usually presenting with symptoms. 4 Reported incidence of meningitis among neonatal sepsis ranges between 0.3-3% while LOS is noted to have a significant association with the presence of meningitis, found in 3-30% of the cases. 6 In all neonates having LOS, lumber puncture (LP) is commonly performed when the clinical status of the individual stabilizes.…”
Section: Introductionmentioning
confidence: 98%
“…LOS is described as systemic infection occurring beyond 1 st 72 hours following birth. 4 Any newborn with bacterial sepsis is also at risk of meningitis. 5 Meningitis is frequently found in LOS cases in comparison to EOS while it is also found that LOS linked meningitis is usually presenting with symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that neonates with sepsis have an increased risk of developing meningitis, which on its own would deteriorates the prognosis of such neonates [5,6]. Data from both high-and low-income settings have shown that meningitis affects 0.3 to 3% of neonates with early onset neonatal sepsis [7,8] and up to 30% of cases with LONS [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%